Evaluating the Dutch Action Plan on Physical Activity From a Systems’ Perspective (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The Dutch Ministry of Health, Welfare and Sport wants to make it easier for people to be active every day. This requires changes to the living environment, like improving cycling paths, and cooperation across domains such as healthcare, education, and workplaces, ranging from local to national level. For this purpose, the Ministry created the Dutch Action Plan on Physical Activity (2023–2025). This Action Plan takes a system approach, addressing all aspects of physical activity (PA) rather than focusing on a single component like sports. The plan contributes to the government’s goal of 75% adherence to the Dutch Physical Activity Guidelines by 2040. The National Institute for Public Health and the Environment (RIVM) evaluates the Action Plan and reported on its progress in the first 1.5 years.Project and Policy Description: Actions and policies have been implemented across three Action Tracks: 1) increasing awareness of PA’s importance among society and policymakers, 2) fostering collaboration in promoting PA through the Physical Activity Network Alliance, and 3) enhancing cross-domain cooperation at local/regional levels. Progress in implementing the three Action Tracks is evaluated based on output in different areas: increased awareness, more (implementation of) cross-domain PA policy, and strengthening of new and existing PA initiatives. This output is expected to contribute to increased PA in the long-term. The interim evaluation shows positive developments in all Action Tracks. An example of a positive development is that within one year, three times as many parties have joined the Physical Activity Network Alliance, now totalling over 400. Furthermore, despite challenges in cross-domain collaboration, parties from different sectors are increasingly working together to promote PA through the living environment, nationally and locally. However, not all plans to encourage PA have yet been translated into concrete actions.Conclusion: This interim evaluation shows early positive developments since the launch of the Action Plan. Yet, continued commitment from all levels is needed to turn plans into action. Structural, long-term policy beyond single government terms is important, as well as time to realise system changes and impact PA behaviour. RIVM therefore advises extending the policy initiatives beyond the Action Plan period.